Effect of sub-technique transitions on energy expenditure and physiological load in the classical-style technique among elite male cross-country skiers - Carlsson, T.; Wedholm, L.; Fjordell, W.; Swarén, M.; Carlsson, M. (European Journal of Applied Physiology, 2021)
Purpose To investigate whether sub-technique transitions in the classical-style technique are associated with increased energy expenditure and/or metabolic stress among elite male cross-country skiers.